Evaluation of Microbiological Performance and the Potential Clinical Impact of the ePlex® Blood Culture Identification Panels for the Rapid Diagnosis of Bacteremia and Fungemia - Bryant, Sabrina; Almahmoud, Iyad; Pierre, Isabelle; Bardet, Julie; Touati, Saber; Maubon, Daniele; Cornet, Muriel; Richarme, Claire; Maurin, Max; Pavese, Patricia; Caspar, Yvan (Frontiers in Cellular and Infection Microbiology, 2020)
Molecular rapid diagnostic assays associated with antimicrobial stewardship have proven effective for the early adaptation of empiric therapy in bloodstream infections. The ePlex® BCID (GenMark Diagnostics) Panels allow identification of 56 bacteria and fungi and 10 resistance genes in 90 min directly from positive blood cultures. We prospectively evaluated 187 sepsis episodes at Grenoble University Hospital and retrospectively analyzed the cases to measure the potential clinical impact of the ePlex BCID results. Identification of all pathogens was obtained for 164/187 (88%) bloodstream infections with 100% detection of antimicrobial resistance genes (17 blaCTX-M, 1 vanA, and 17 mecA genes). Only 15/209 (7%) strains were not covered by the panels. Sensitivity for detection of micro-organisms targeted by the RUO BCID-GP, BCID-GN, and BCID-FP Panels was respectively 84/84 (100%), 103/107 (96%), and 14/14 (100%). Interestingly, accurate identification of all pathogens was achieved in 15/17 (88%) polymicrobial samples. Retrospective analysis of medical records showed that a modification of antimicrobial treatment would have been done in 45% of the patients. Treatment modifications would have been an optimization of empiric therapy, a de-escalation or an escalation in respectively 16, 17, and 11% of the patients. Moreover, 11% of the samples were classified as contaminants or not clinically relevant and would have led to early de-escalation or withdrawal of any antibiotic. Detection of resistance genes in addition to identification alone increased escalation rate from 4 to 11% of the patients. Absence of the ePlex result was considered a lost opportunity for therapy modiﬁcation in 28% of patients.